2020
DOI: 10.3389/fmicb.2020.00727
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of the O-Antigen and Development of a Molecular Serotyping Scheme for Enterobacter cloacae

Abstract: Enterobacter cloacae is a well-characterized opportunistic pathogen that is closely associated with various nosocomial infections. The O-antigen, which is one of the most variable constituents on the cell surface, has been used widely and traditionally for serological classification of many gram-negative bacteria. E. cloacae is divided into 30 serotypes, based on its O-antigen diversity. In this study, by using genomic and comparative-genomic approaches, we analyzed the O-antigen gene clusters of 26 E. cloacae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Interestingly, intact ENT47670 prophage, which also contained structural phage proteins, was detected in the prophage region where gtrA and gtrB were harbored (see Data Sets S3 and S5). This result indicates that gtrA and gtrB of the prophage region in E. cloacae were acquired through the transduction of ENT47670 or ENT47670-like phages ( 34 ).…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, intact ENT47670 prophage, which also contained structural phage proteins, was detected in the prophage region where gtrA and gtrB were harbored (see Data Sets S3 and S5). This result indicates that gtrA and gtrB of the prophage region in E. cloacae were acquired through the transduction of ENT47670 or ENT47670-like phages ( 34 ).…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, intact ENT47670 prophage, which also contained structural phage proteins, was detected in the prophage region where gtrA and gtrB were harbored (Data Set S5). This result suggested that gtrA and gtrB of the prophage region in E. cloacae were acquired through the transduction of ENT47670 or ENT47670-like phages (32) (Fig. 5; Data Set S5).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for SU7’s narrow host range could be its host receptor. The most common phage-host receptor for Podoviridae coliphages is the O-polysaccharide antigen of the lipopolysaccharide layer [ 55 , 56 , 57 ], which is highly variable in the Enterobacter genus [ 58 ]. It should be noted that despite being a rapid, simple, and quantitative screen, single high titer spot testing to determine host range may fail to discriminate between a phage’s ability to replicate within a host and its ability to kill the host strain, as well as result in an overestimation of phage host range and virulence [ 51 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%